A Mini-Review on Current Management Options in Caesarean Scar Ectopic Pregnancy - M. Asiri (Issues and Developments in Medicine and Medical Research Vol. 3, 2022)
The diagnosis of scar ectopic pregnancy is challenging as the patient presentations vary considerably, with one-third of patients remaining asymptomatic at diagnosis. Several treatment modalities have been utilized to treat scar ectopic pregnancy. Many surgical strategies are represented to treat patients with scar ectopic pregnancy, including D&C; excision of scar ectopic pregnancy via abdominal, laparoscopic, or hysteroscopic. However, definitive management is through hysterectomy.